Evaluation of triglyceride-glucose index with cardiovascular risk scoring in schizophrenia patients - Uslu, Muhammed Fuad; Tabara, Muhammed Fatih; Yildiz, Sevler; Hekim, Alaaddin (Bayrakol Medical Publisher, 2025)
Aim: Schizophrenia patients who are at risk for cardiovascular diseases are often hospitalized in forensic psychiatry wards due to crimes they have committed. In this study, we evaluated schizophrenia patients in a forensic psychiatry service regarding cardiovascular risk scoring using the triglyceride-glucose index. Material and Methods: The study included 51 healthy controls and 51 patients with schizophrenia receiving treatment in a forensic psychiatry service, resulting in 102 participants. The Triglyceride-Glucose Index [fasting triglyceride (mg/dL) x fasting plasma glucose (mg/dL) / 2] and the Framingham Risk Score were calculated for all participants. The relationship between these values and clinical variables was then analyzed. Results: BMI, platelet count, triglyceride, and total cholesterol values were significantly higher, while urea and creatinine values were significantly lower in the case group compared to the control group. The Framingham score and 10-year CVD risk score of the case group were significantly higher than the control group, while the groups were similar in terms of Triglyceride-Glucose index (p<0.001; p<0.001; p=0.066, respectively). The groups were similar according to the type of crime committed (p>0.05). There was a significant positive correlation between the duration of schizophrenia and Framingham score and 10-year CVD risk score (p<0.001; p<0.001, respectively). Discussion: We propose that close monitoring of schizophrenia patients for cardiovascular diseases in forensic psychiatry wards, where long-term hospitalizations are common, may contribute to reducing mortality and morbidity.
Keywords: Schizophrenia; Triglyceride-Glucose Index; Cardiovascular Risk; Framingham Scoring